STUDI TERJEMAH AL QURAN KAWASAN ASIA TENGGARA - Arjuna, Klawing; Munfarida, Elya (STAI Asy-Syukriyyah, 2023)
Translation of the Quran is an important topic to be studied academically as the transfer of language from the source language to the target language is not an easy task. Translation must also take into account the culture, social conditions, and language used to render the language of the Quran into a language understandable by the people in the Southeast Asian region. The purpose of this research is to enhance the understanding and accessibility of the language of the Quran in the Southeast Asian region. Through this study, it is revealed that the translation of the Quran originated from the Malay region of Sumatra and later spread throughout Southeast Asia through various Quranic scholars who studied the Quran in the Arabian Peninsula, the place where the Quran was revealed.